Indoor methane consistently above outdoor levels in homes with natural gas service - Nathan G. Phillips; Robert Ackley; Andee Krasner (PLoS ONE, 2026)
Background Methane leaks across the natural gas process chain, including in homes. To date, no studies have described how common it is to have elevated methane in homes served by gas, in comparison to homes without gas. Methods In this study of homes in Massachusetts and Rhode Island, we utilized Cavity Ringdown Spectrometry to measure methane concentrations in outdoor air, and at mid-floor-level indoor air in basements and first, second, and third floors. We recruited a total of 195 homes in urban and rural areas, 175 of which had gas service and 20 of which did not. Results Indoor [CH 4 ] in households with gas service was elevated over outdoor [CH 4 ], averaging 1.45 parts per million (ppm) elevation over outdoor ambient [CH 4 ] (p < 0.0001–0.0068), and up to 38.2 ppm above outdoor ambient [CH 4 ]. Ninety-three percent of homes with gas showed higher median indoor [CH 4 ] than the median [CH 4 ] in non-gas homes. By contrast, indoor [CH 4 ] in gas-free homes did not differ from outdoor conditions (p > 0.10), except marginally on the first floor (0.10 ppm elevation; p = 0.04). In 91% of a subset of homes investigated, leaks from gas equipment were confirmed. Conclusions Elevated [CH 4 ] is common in homes served with gas. Gas leaks and incomplete combustion were identified as sources of elevated [CH 4 ]. There was no relationship between indoor [CH 4 ] and home age or square footage; residents shouldn’t assume that newer homes are less prone to indoor gas leaks. The majority of gas in the United States comes from hydraulically fractured gas containing carcinogenic co-pollutants. It is not well understood how consistent low-dose exposure to gas co-pollutants like mercaptans and benzene affects health. Additional studies could clarify any differences in health outcomes for people living in homes serviced by gas and those who don’t use gas.